Breast cancer detection among Irish BRCA1 & BRCA2 mutation carriers: a population-based study. (February 2016) - Walsh, E.; Farrell, M.; Nolan, C.; Gallagher, F.; Clarke, R.; McCaffrey, J.; Kennedy, M.; Barry, M.; Kell, M.; Gallagher, D.
Abstract Background High-risk breast cancer screening forBRCA1/2 mutation carriers with clinical breast exam, mammography and MRI has reported sensitivity of 100 %, butBRCA1/2 mutation carriers still present with interval cancers. Aims We investigated the presentation and screening patterns of an Irish cohort ofBRCA1/2 mutation carriers with breast cancer. Materials and methods BRCA1/2 mutation carriers with breast cancer were identified in this retrospective cohort study. Records were reviewed forBRCA1/2 mutation status, demographics, screening regimen, screening modality, stage and histology at diagnosis. Results Fifty-three cases of breast cancer were diagnosed between 1968 and 2010 among 60 Irish hereditary breast ovarian cancer (HBOC) families. In 50 of 53 women, the diagnosis of breast cancer predated the identification ofBRCA1/2 mutations. Breast cancer detection method was identified in 47 % of patients (n  = 25): 80 % (n  = 20) by clinical breast exam (CBE), 12 % by mammography (n  = 3), 8 % by MRI (n  = 2). Fourteen women (26 %) developed a second breast cancer. Ten of these patients (71 %) were involved in regular screening; 50 % were detected by screening mammography, 20 % by MRI and 30 % by CBE alone. Six patients (43 %) had a change in morphology from first to second breast cancers. There was no change in hormone receptor status between first and second breast cancers. Conclusion In this cohort of Irish BRCA1/2 mutation carriers, compliance with screening was inconsistent. There was a 30 % incidence of interval cancers occurring in women in high-risk screening. Preventive surgery may be a more effective risk reduction strategy for certain high-risk women.